2008
DOI: 10.1080/03079450802499100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative infectiousness of three passerine bird species after experimental inoculation withMycoplasma gallisepticum

Abstract: Mycoplasma gallisepticum has been isolated from various species of free-living birds, and we therefore tested the hypothesis that bird species other than the main host, the house finch (Carpodacus mexicanus), could play a role in the epidemiology of the infection. We compared the disease course in the house finch, American goldfinch (Carduelis tristis) and house sparrow (Passer domesticus) after inoculation into the conjunctival sac with M. gallisepticum, and also the degree to which the three species were inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…M. gallisepticum isolated from house finches can be transmitted from infected sparrows to finches up to 3 d.p.i. (Dhondt et al, 2008). Other studies showed that M. gallisepticum from house finches caused seroconversion in sparrows (by SPA) but it could not be cultured (Farmer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…M. gallisepticum isolated from house finches can be transmitted from infected sparrows to finches up to 3 d.p.i. (Dhondt et al, 2008). Other studies showed that M. gallisepticum from house finches caused seroconversion in sparrows (by SPA) but it could not be cultured (Farmer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are also experimental infections described in the literature using a virulent laboratory strain of M. gallisepticum (Kleven & Fletcher, 1983) or a house finch strain of M. gallisepticum (Farmer et al, 2005;Dhondt et al, 2008), with the latter described as mildly pathogenic to chickens (O'Connor et al, 1999). M. gallisepticum strains vary in virulence and infectivity as well as in their ability to persist in respiratory tissues (Ley, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations